Optimization of the Public Prosecutor’s Function as Dominus Litis in Preventing Repeated Returns of Case Files - Egy Chandra Nur Sandya; Anik Tri Haryani; Krista Yitawati (Universitas Merdeka Madiun, 2026)
Introduction to the Problem: The repeated return of criminal case files by public prosecutors to investigators remains a procedural problem in Indonesia’s criminal justice system. This practice reflects weak coordination between investigators and prosecutors, differences in evidentiary interpretation, and the absence of clear procedural limitations regarding the return of case files. Such conditions hinder legal certainty, delay criminal proceedings, and negatively affect the protection of human rights. Purpose/Study Objectives: This study aims to analyze the optimization of the public prosecutor’s function as dominus litis in preventing repeated returns of criminal case files within the Indonesian criminal justice system. Design/Methodology/Approach: This research employs a normative legal research method using statutory and conceptual approaches. Legal materials consist of primary, secondary, and tertiary legal sources collected through library research and analyzed qualitatively using a descriptive-analytical method. Findings: The study reveals that the repeated return of criminal case files is caused by weak coordination between investigators and prosecutors, differing interpretations regarding evidentiary standards, limited prosecutorial involvement during investigations, and regulatory gaps within the Indonesian Criminal Procedure Code (KUHAP). The optimization of the prosecutor’s function as dominus litis may be achieved through strengthening prosecutorial authority in supervising investigations, improving institutional coordination from the issuance of the Notice of Commencement of Investigation (SPDP), harmonizing evidentiary standards, reforming criminal procedural law, and implementing integrated digital case administration systems. These measures are expected to increase efficiency, legal certainty, accountability, and public trust within Indonesia’s criminal justice system.